Rethinking Justice: A Critique of J. Rawls's Theory - Деркач, Вадим Леонтійович (Київський національний університет імені Тараса Шевченка, 2025)
This article offers a critical re-evaluation of John Rawls’s theory of justice. Key elements of Rawls’s framework, including the notions of the “original position”, the “veil of ignorance”, and the “difference principle”, are examined and highlighted for their detachment from actual social sentiments and conflicts. Employing conceptual analysis and game-theoretical modeling, the study demonstrates that Rawls’s procedural approach cannot fully circumvent internal antinomies. The paper proposes an alternative conception according to which justice is not about leveling, but about justified inequality. This model grounds social privileges in the individual’s contribution, competence, and responsibility, which, the author argues, ensures the evolutionary stability and productivity of social systems. The advantages of this approach are demonstrated in comparison to Rawls’s framework, which, while guaranteeing basic protection, may inadvertently weaken incentives for personal and societal development.

Стаття є критичним переосмисленням теорії справедливості Дж. Роулза. Розібрані ключові положення Роулзової концепції, зокрема, ідеї "первинної позиції", "ширми непередбачуваності" та "принципу різниці", відзначаючи їхню відірваність від реальних соціальних почуттів і конфліктів. Використовуючи методологію концептуального аналізу та ігрового моделювання, показано, що процедурний підхід Роулза не може уникнути внутрішніх антиномій. У роботі пропонується альтернативна концепція, згідно з якою справедливість — це не вирівнювання, а виправдана нерівність. Вона базується на відповідності соціальних привілеїв внеску, компетенції та відповідальності індивіда, що, на думку автора, забезпечує еволюційну стійкість і продуктивність суспільних систем. Демонструється перевага такої моделі перед Роулзовою, яка, хоч і гарантує базовий захист, може послаблювати стимули до розвитку.
Переосмислення справедливості: критика теорії Дж. Роулза
Keywords: justice; John Rawls; theory of justice; utilitarianism; rational choice; social inequality; compensation; hierarchy; institutional justice; political philosophy; справедливість; Джон Роулз; теорія справедливості; утилітаризм; раціональний вибір; соціальна нерівність; компенсація; ієрархія; інституційна справедливість; політична філософія